Pengaruh Perbedaan dari Laba Akuntansi, Laba Fiskal dan Komponen Laba terhadap Persistensi Laba pada Perusahaan yang Terdaftar di BEI - Febianty, Evania; Kurniawan, Budi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
The motivation behind this study is to inspect the contrast between bookkeeping benefit and available benefit and current profit parts. The contrast between bookkeeping benefit and expense benefit is situated by utilizing the distinction between bookkeeping benefit and duty benefit which is positive and the contrast between bookkeeping benefit and assessment benefit which is negative. The parts of current profit examined are incomes and accumulations. Income is estimated from working income, while gatherings are estimated from the distinction between bookkeeping benefit before charge less working income. Benefit ingenuity is situated with bookkeeping benefit before charge. The examining strategy utilized in this exploration is purposive testing technique. The consequences of the investigation show that the distinction between bookkeeping benefit and financial benefit is positive and working income altogether affects profit industriousness. Gatherings affect income tirelessness. In the interim, the contrast between bookkeeping benefit and available benefit is negative and doesn't altogether affect profit constancy.